2008
DOI: 10.1007/s00423-008-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of major abdominal surgery on endotoxin release and expression of Toll-like receptors 2/4

Abstract: Major abdominal surgery is associated with endotoxemia, reduced capability of plasma to inactivate endotoxin, cytokine kinetics resembling those of healthy man after experimentally given LPS, and substantial acute-phase reaction. The cytokine liberation of mononuclear cells suggests a state of postoperative endotoxin tolerance. Despite these substantial changes, trends in TLR2/4 expression are not obvious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…For example, lung inflammation may be reduced by PEEP and lower tidal volumes49, despite the presence of a pro-inflammatory response even during mild mechanical ventilation50. Also, in contrast to controlled ventilation, noisy pressure support ventilation could modify inflammation by changing lung mechanics and gas exchange25, 26; 3) effects of mechanical ventilation in normal and injured lungs: mechanical ventilation with low and high tidal volumes affect lungs differently, depending on their previous degree of injury51, 52. Consequently, regional inflammation magnitude and distribution may differ in the case of previously injured lungs or lungs affected by other injurious mechanisms51; 4) interference with anesthesia: because both inhaled53 and intravenous54, 55 anesthetic agents can modulate inflammation, use of different anesthetic regimens could modify the observed inflammatory pattern.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lung inflammation may be reduced by PEEP and lower tidal volumes49, despite the presence of a pro-inflammatory response even during mild mechanical ventilation50. Also, in contrast to controlled ventilation, noisy pressure support ventilation could modify inflammation by changing lung mechanics and gas exchange25, 26; 3) effects of mechanical ventilation in normal and injured lungs: mechanical ventilation with low and high tidal volumes affect lungs differently, depending on their previous degree of injury51, 52. Consequently, regional inflammation magnitude and distribution may differ in the case of previously injured lungs or lungs affected by other injurious mechanisms51; 4) interference with anesthesia: because both inhaled53 and intravenous54, 55 anesthetic agents can modulate inflammation, use of different anesthetic regimens could modify the observed inflammatory pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, postural changes, blood loss, and vasoplegia all cause relative or absolute hypoperfusion that may favor bacterial translocation. Buttenschoen and colleagues have in fact shown that major abdominal surgery is associated with transient endotoxemia [ 13 , 14 ]. However, while the likelihood of endotoxemia might be straightforward in major abdominal surgery, less is known in other surgical procedures, apart from cardiopulmonary bypass [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the postoperative period, the pattern of cytokine release by human immune competent cells suggests postoperative endotoxin tolerance [21]. As shown by Sato et al [12], this effect is not restricted to pre-treatment with TLR4-agonists, as R-848 pre-treated peritoneal macrophages synthesize lower amounts of pro-inflammatory cytokines on stimulation with LPS.…”
Section: Discussionmentioning
confidence: 61%